2014
DOI: 10.1128/ec.00215-14
|View full text |Cite
|
Sign up to set email alerts
|

Hammondia hammondi Harbors Functional Orthologs of the Host-Modulating Effectors GRA15 and ROP16 but Is Distinguished from Toxoplasma gondii by a Unique Transcriptional Profile

Abstract: Toxoplasma gondii and its nearest extant relative, Hammondia hammondi, are phenotypically distinct despite their remarkable similarity in gene content, synteny, and functionality. To begin to identify genetic differences that might drive distinct infection phenotypes of T. gondii and H. hammondi, in the present study we (i) determined whether two known host-interacting proteins, dense granule protein 15 (GRA15) and rhoptry protein 16 (ROP16), were functionally conserved in H. hammondi and (ii) performed the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Clearly then, the presence of a given virulence effector in the H. hammondi genome is not sufficient to explain its highly avirulent phenotype in mice . We have also shown that H. hammondi ROP18, ROP5, ROP16 and GRA15 are functional effectors when expressed in relevant T. gondii genetic backgrounds . Specifically, H. hammondi has a functional ROP18 ortholog that is highly effective at increasing the virulence of essentially ROP18‐null T. gondii strains (such as the type III strain CTG; ).…”
Section: Conservation Of Known T Gondii Secreted Effectors In H Hammentioning
confidence: 92%
See 3 more Smart Citations
“…Clearly then, the presence of a given virulence effector in the H. hammondi genome is not sufficient to explain its highly avirulent phenotype in mice . We have also shown that H. hammondi ROP18, ROP5, ROP16 and GRA15 are functional effectors when expressed in relevant T. gondii genetic backgrounds . Specifically, H. hammondi has a functional ROP18 ortholog that is highly effective at increasing the virulence of essentially ROP18‐null T. gondii strains (such as the type III strain CTG; ).…”
Section: Conservation Of Known T Gondii Secreted Effectors In H Hammentioning
confidence: 92%
“…Importantly, the STAT6 induction was significantly higher than type II T. gondii expressing an additional copy of a type II ROP16 allele, providing strong evidence that the ‘active’ allele of ROP16 with respect to STAT6 activation is ancestral to the T. gondii / H. hammondi split. Interestingly, however, the H. hammondi ROP16 gene promoter had a 16 bp deletion compared to T. gondii ROP16, and this 16 bp was essential for ROP16 promoter function . It is therefore possible that in H. hammondi ROP16 is fully functional with respect to STAT6 activation, but is poorly expressed.…”
Section: Conservation Of Known T Gondii Secreted Effectors In H Hammentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, one important prerequisite is that peptides applied in such tests are not specific for particular clonal-types or genotypes of T. gondii or related parasite species. In addition, potential cross-reactivities need to be addressed; for instance, synthetic peptides considered to react specifically with antibodies generated by T. gondii infections need to be tested with sera from animals exposed to H. hammondi , as this parasite has a very close genetic relationship to the former (Walzer et al 2013, 2014). The use of T. gondii -specific peptides for diagnosis in animals should also be tested with N. caninum , which may cross-react, as shown in Table 3.…”
Section: Serology For T Gondii and Cross-reactivity With Related Patmentioning
confidence: 99%